Advancing Passwordless Authentication: A Systematic Review of Methods, Challenges, and Future Directions for Secure User Identity - Mohd Imran Md Yusop; Nazhatul Hafizah Kamarudin; Nur Hanis Sabrina Suhaimi; Mohammad Kamrul Hasan (IEEE Access)
As reliance on digital services grows, traditional password-based authentication methods have been increasingly scrutinized due to their susceptibility to cyber-attacks, including phishing and brute force attacks. This has led to a shift toward passwordless authentication, an approach that promises enhanced security and user experience. This paper provides a comprehensive review of passwordless authentication techniques, analysing their application in user identity verification across multiple platforms. Various methods such as biometrics, security keys, and token-based systems are explored for their efficacy in mitigating security vulnerabilities. The review highlights the advantages of passwordless authentication, including improved security, reduced user friction, and compatibility with modern identity management frameworks like FIDO2. Challenges such as usability issues, cost of deployment, and scalability are also discussed. Moreover, the paper identifies future research areas aimed at overcoming these challenges and facilitating the broad adoption of passwordless authentication in critical industries such as healthcare, finance, and public services. Future opportunities are outlined, emphasizing the need for real-world implementation, enhanced scalability, integration of AI-driven adaptive mechanisms, and innovative designs to improve user accessibility and system resilience. By consolidating existing knowledge and identifying gaps in current solutions, this study provides valuable insights for researchers and industry stakeholders seeking to enhance security through passwordless systems.